Polymer resin and preparation method thereof, optical lens and intelligent glasses

By using polymeric resins with thioamide groups, thioether groups and aromatic groups, the problems of poor oxidation resistance and stability of existing optical resin materials are solved, and high refractive index, good light transmittance and excellent mechanical properties are achieved, simplifying the synthesis process and reducing production costs.

CN119842037APending Publication Date: 2025-04-18ZHUHAI MOJIE TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411950847.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

While increasing the refractive index, existing optical resin materials have poor oxidation resistance and stability, and are complex in synthesis and difficult to process.

Method used

Using a polymeric resin including thioamide groups, thioether groups and aromatic groups, it is prepared by reactions of thiocyanate, thio compound, organic base catalyst and solvent to simplify the synthesis process and improve the oxidation resistance and stability.

Benefits of technology

The polymer resin has achieved high refractive index, good light transmittance, excellent mechanical properties, heat resistance and low shrinkage, while improving oxidation resistance and stability, reducing process difficulty and production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842037A_ABST
    Figure CN119842037A_ABST
Patent Text Reader

Abstract

The invention discloses a polymer resin and a preparation method thereof, an optical lens and intelligent glasses, and relates to the technical field of resin materials. The polymer resin comprises a thioamide group, a thioether group and an aromatic group, and is prepared from the following raw materials: thiocyanate, a sulfhydryl compound, an organic base catalyst and a solvent. The oxidation resistance and the stability of the polymer resin can be improved, and the polymer resin also has high refractive index performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of resin materials, and in particular to a polymer resin and a preparation method thereof, optical lenses and smart glasses. Background Art

[0002] Optical materials are mainly divided into two categories: glass and resin, and are widely used in many fields such as display, lens, sensor, etc. Among them, optical resin materials are gaining more and more attention in the field of optical materials due to their advantages such as low specific gravity, high impact toughness, rich structural design, and easy processing. Refractive index is one of the most important indicators reflecting optical resin materials. A higher refractive index can effectively improve light efficiency, reduce lens thickness, reduce costs, and obtain a good wearing experience.

[0003] The related technology generally adopts the method of introducing hydroxyl groups into the benzene ring of polyphenylene sulfide to increase the refractive index of the polymer resin. However, the synthesis process of hydroxyl-modified polyphenylene sulfide is complicated, and the benzene ring is easily oxidized, which causes the polymer resin to turn yellow, deteriorate in solubility and reduce molecular weight, thereby making the polymer resin less resistant to oxidation and less stable, and difficult to process. Summary of the invention

[0004] Based on this, the present application provides a polymer resin and a preparation method thereof, an optical lens and smart glasses, which can improve the oxidation resistance and stability of the polymer resin while also having high refractive index performance.

[0005] In a first aspect, the present application provides a polymer resin having the following general structural formula:

[0006]

[0007] In the formula, R 1 , R 2 At least one of them is an aromatic group, and n is a positive integer of 1-10000.

[0008] In a second aspect, the present application provides a polymer resin, which is prepared from the following raw materials: thiocyanate, a mercapto compound, an organic base catalyst and a solvent.

[0009] In a third aspect, the present application provides a method for preparing a polymer resin, the method comprising:

[0010] Providing thiocyanate, mercapto compound, organic base catalyst and solvent;

[0011] The thiocyanate, the mercapto compound, the organic base catalyst and the solvent are stirred uniformly to react to obtain a polymer resin.

[0012] In a fourth aspect, the present application provides an optical lens, which is made of the polymer resin as described above, or made of a polymer resin prepared by the method for preparing the polymer resin as described above.

[0013] In a fifth aspect, the present application provides a pair of smart glasses, comprising the optical lenses as described above.

[0014] The embodiment of the present application provides a polymer resin and a preparation method thereof, an optical lens and smart glasses. The polymer resin includes three structures of a thioamide group, a thioether group and an aromatic group, and has a high refractive index, good light transmittance, good mechanical properties, heat resistance and low shrinkage. At the same time, the hydrogen bond acceptor and hydrogen bond donor of the polymer resin provided by the present application are both located in the main chain structure of the polymer resin, and the introduction process does not require an additional modification step, thereby simplifying the synthesis process, and the raw materials provided by the present application are easy to obtain and have high activity. Only an organic base catalyst can be used to react, and no organic metal catalyst is required. The reaction conditions are simple, which reduces the process difficulty and production cost. In addition, by directly embedding the hydrogen bond acceptor and the hydrogen bond donor into the main chain, its solubility can be optimized, the molecular weight of the polymer resin can be increased, and its thermal stability and processing performance can be improved. In addition, since the hydrogen bond acceptor and the hydrogen bond donor are directly embedded in the main chain structure of the polymer resin, the active sites can be greatly reduced or eliminated, thereby improving the antioxidant and stability of the polymer resin and reducing the probability of yellowing. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 A schematic flow chart of the steps of a method for preparing a polymer resin provided in an embodiment of the present application. DETAILED DESCRIPTION

[0016] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0017] The flowcharts shown in the accompanying drawings are only examples and do not necessarily include all the contents and operations / steps, nor must they be executed in the order described. For example, some operations / steps may also be decomposed, combined or partially merged, so the actual execution order may change according to actual conditions.

[0018] In the subsequent description, the suffixes such as "module", "component" or "unit" used to represent elements are only used to facilitate the description of the present application, and have no special meanings. Therefore, "module", "component" or "unit" can be used in a mixed manner.

[0019] The related technology generally adopts the method of introducing hydroxyl groups into the benzene ring of polyphenylene sulfide to increase the refractive index of the polymer resin. However, the synthesis process of hydroxyl-modified polyphenylene sulfide is complicated, and the hydroxyl groups on the benzene ring may become active sites for oxidation reactions, which may cause the resin to easily undergo oxidation reactions under light, high temperature or oxygen, thereby causing yellowing, and also making the solubility of the resin worse and the molecular weight lower, thereby making the polymer resin less resistant to oxidation and less stable, and difficult to process.

[0020] To solve the above-mentioned problems, the embodiments of the present application provide a polymer resin and a preparation method thereof, an optical lens and a smart glasses. The polymer resin has a high refractive index, good light transmittance, good mechanical properties, heat resistance and low shrinkage rate, and the raw materials are easy to obtain and have high activity. The reaction can occur using only an organic base catalyst without the need for an organic metal catalyst. The reaction conditions are simple, the synthesis process is simple, the process difficulty and the production cost are low, and the polymer resin has good antioxidant properties and stability.

[0021] The embodiments of the present application are described in detail below with reference to the accompanying drawings.

[0022] The present application provides a polymer resin having the following general structural formula:

[0023]

[0024] In the formula, R 1 , R 2 At least one of them is an aromatic group, and n is a positive integer of 1-10000.

[0025] The polymer resin includes three structures: a thioamide group, a thioether group and an aromatic group. The structural formula of the thioamide group is as follows:

[0026]

[0027] The structural formula of the thioether group is as follows:

[0028]

[0029] Wherein, the thioamide group includes a sulfur atom and an NH bond, and the thioether group includes a sulfur atom. The sulfur atom in the thioamide group and the thioether group is a group with a high molar refractive index, and the propagation speed of light will slow down when passing through, thereby increasing the refractive index. Moreover, under the joint action of the sulfur atoms in the thioamide group and the thioether group, the effect of increasing the refractive index is more obvious. The nitrogen atom in the NH bond can be used as a hydrogen bond acceptor, and the hydrogen bond acceptor is conducive to forming hydrogen bonds, thereby enhancing the intermolecular forces of the resin, achieving the effect of dense atomic accumulation, and thus being able to increase the refractive index. The thioamide group provided in the present application has two NH bonds, which can further enhance the intermolecular forces of the resin, thereby being able to further increase the refractive index.

[0030] For example, R 1 It can be an aromatic group, R 2 It can be any group other than an aromatic group; R 2 It can be an aromatic group, R 1 It can be any group other than an aromatic group; R 1 and R 2 They may all be aromatic groups. n represents an integer of 1-10000, for example, n is 1, 75, 170, 650, 4500, 7500, 10000, etc.

[0031] The polymer resin provided in the embodiment of the present application has an ultra-high refractive index. On the one hand, this is due to the high degree of unsaturation in the structure of the polymer resin, such as the six-membered aromatic ring contained in the aromatic group. Due to the presence of unsaturated double bonds in the aromatic group, the resin can form a more compact network structure during the curing process, thereby increasing the refractive index of the polymer resin, and the thioamide group and the thioether group both have a high sulfur atom ratio. Sulfur itself is a group with a high molar refractive index. The propagation speed of light will slow down when passing through, thereby increasing the refractive index; on the other hand, it is due to abundant hydrogen bond acceptors and abundant hydrogen bond donors. The hydrogen bond acceptors may include nitrogen atoms in thiocarbonyl, thioether group, and thioamide group, and the hydrogen bond donors may include thioamide groups. Since the polymer resin has atoms with strong electronegativity (such as oxygen, nitrogen or sulfur), these atoms are easy to form hydrogen bonds, and hydrogen bonds can also be formed between the groups. Therefore, under the action of multiple hydrogen bonds with varying strengths, the intermolecular forces of the resin can be enhanced, thereby achieving the effect of dense atomic stacking, thereby further improving the refractive index, so that the refractive index of the polymer resin can reach above 1.8.

[0032] Secondly, the polymer resin provided in the embodiment of the present application also has good light transmittance. On the one hand, due to the large atomic radius of sulfur atoms, it is difficult to form a conjugated structure between groups / atoms and groups / groups, and the light absorption is weak; on the other hand, the rich variety and varying strength of hydrogen bonds in the polymer resin can effectively avoid the formation of an ordered crystalline structure between resin molecules, but form an amorphous stacking structure, thereby effectively avoiding light scattering and enhancing light transmittance.

[0033] In addition, the polymer resin provided in the embodiments of the present application also has good mechanical properties, heat resistance and low shrinkage. This is because the rigid structure of the aromatic group and the low chain freedom of the polymer molecule can greatly improve the mechanical properties and heat resistance of the polymer resin, and can also effectively reduce the shrinkage of the polymer resin.

[0034] Since the polymer resin provided by the embodiment of the present application includes three structures of thioamide group, thioether group and aromatic group, the polymer resin has a higher refractive index, good light transmittance and good mechanical properties, heat resistance and low shrinkage. At the same time, the hydrogen bond acceptor and hydrogen bond donor of the polymer resin provided by the present application are both located in the main chain structure, and the introduction process does not require additional modification steps, thereby simplifying the synthesis process, and the raw materials provided by the present application are easy to obtain and have high activity, and only organic base catalysts can be used to react, without the use of organic metal catalysts, and the reaction conditions are simple, which reduces the process difficulty and production cost. In addition, by directly embedding the hydrogen bond acceptor and hydrogen bond donor into the main chain, due to the large hydrogen bond force, the polarity of the molecule is relatively strong, so that the solubility of the polymer resin in polar solvents becomes stronger, so that its solubility can be optimized, and the molecular weight of the polymer resin can also be improved, and the improvement of the molecular weight improves its thermal stability and processing performance. In addition, since the hydrogen bond acceptor and hydrogen bond donor are directly embedded in the main chain structure of the polymer resin, the active sites can be greatly reduced or eliminated, thereby improving the antioxidant and stability of the polymer resin and reducing the probability of yellowing.

[0035] In some embodiments, R 1 and R 2 All of them are aromatic groups.

[0036] In R 1 and R 2 When all of them are aromatic groups, the unsaturation of the polymer resin can be increased. Due to the presence of unsaturated double bonds in the aromatic groups, the resin can form a tighter network structure during the curing process, thereby improving the refractive index, light transmittance, mechanical properties and heat resistance of the polymer resin, and reducing the shrinkage rate of the polymer resin.

[0037] In some embodiments, the aromatic group can be selected from one or more of a benzene ring, a naphthalene ring, fluorene, carbazole, furan, thiophene, pyrrole, thiazole, imidazole, pyridine, pyrazine, pyrimidine, and pyridazine.

[0038] In some embodiments, the polymer resin provided herein is selected from any one of structural formulas P1-P5.

[0039] in:

[0040] P1:

[0041] P2:

[0042] P3:

[0043] P4:

[0044] The general structural formula provided by this application is described below: The raw material composition for preparing the polymer resin.

[0045] The polymer resin is prepared from the following raw materials: thiocyanate, mercapto compound, organic base catalyst and solvent.

[0046] In the embodiment of the present application, raw materials such as thiocyanate, mercapto compound, organic base catalyst and solvent are used for reaction, and a polymer resin including thioamide group, thioether group and aromatic group can be prepared, so that the polymer resin has a high refractive index, good light transmittance, good mechanical properties, heat resistance and low shrinkage. Moreover, the raw materials provided by the present application are easy to obtain, highly active, and have simple reaction conditions. Only organic base catalysts can be used to react without the use of organic metal catalysts, and hydrogen bond acceptors and hydrogen bond donors are located in the main chain structure of the polymer resin. The introduction process does not require additional modification steps, thereby simplifying the synthesis process, reducing the process difficulty and production cost. Moreover, since the preparation method can directly embed hydrogen bond acceptors and hydrogen bond donors into the main chain, it can also optimize its solubility, increase the molecular weight of the polymer resin, and improve its thermal stability and processing performance. In addition, since the hydrogen bond acceptors and hydrogen bond donors are directly embedded in the main chain structure of the polymer resin, the hydrogen bond force is large and the polarity of the molecule is strong, which makes the solubility of the polymer resin in polar solvents stronger and can also increase the molecular weight of the polymer resin. The increase in molecular weight can improve its thermal stability and processing performance. In addition, since the hydrogen bond acceptors and hydrogen bond donors are directly embedded in the main chain structure of the polymer resin, the active sites can be greatly reduced or eliminated, thereby improving the antioxidant properties and stability of the polymer resin and reducing the probability of yellowing.

[0047] In some embodiments, the molar ratio of thiocyanate, thiol compound, organic base catalyst and solvent is (300-350):300:(1-2):(23000-24000).

[0048] For example, the molar ratio of thiocyanate, amino compound, organic base catalyst and solvent may be 330:300:1.6:24000.

[0049] For example, the molar ratio of thiocyanate, amino compound, organic base catalyst and solvent may be 340:300:1.8:23800.

[0050] For example, the molar ratio of thiocyanate, amino compound, organic base catalyst and solvent may be 350:300:2:23600.

[0051] Preferably, the molar ratio of thiocyanate, mercapto compound, organic base catalyst and solvent is (300-305):300:(1-1.5):(23300-23350).

[0052] For example, the molar ratio of thiocyanate, thiol compound and solvent may be 300:300:1:23300.

[0053] For example, the molar ratio of thiocyanate, thiol compound and solvent may be 305:300:1.5:23350.

[0054] For example, the molar ratio of thiocyanate, thiol compound and solvent may be 303:300:1.2:23320.

[0055] For example, the molar ratio of thiocyanate, thiol compound and solvent may be 300:300:1.3:23350.

[0056] For example, the molar ratio of thiocyanate, thiol compound and solvent may be 301:300:1.25:23325.

[0057] For example, the molar ratio of thiocyanate, thiol compound and solvent may be 302:300:1.4:23340.

[0058] It can be understood that the present application can achieve full synergistic effect of the components by reasonably controlling the molar ratio of each component, and avoid the performance degradation of the final polymer resin due to excessive or insufficient amount of a certain component, thereby ensuring that the comprehensive performance of the final polymer resin is better.

[0059] The following description is based on the assumption that the molar amount of the mercapto compound is 300.

[0060] For example, by controlling the molar amount of thiocyanate to 300-305, thiocyanate can react with mercapto compounds to form a polymer resin having thioamide groups, thioether groups and aromatic groups, and the hydrogen bond acceptors and hydrogen bond donors of the polymer resin are both located in the main chain structure of the polymer resin.

[0061] For example, by controlling the molar amount of the solvent to 23300-23350, the solvent can fully wet other components and make the components mutually soluble to form a relatively uniform mixed system, which is convenient for preparing the polymer resin.

[0062] For example, by controlling the molar amount of the organic base catalyst to 1 to 1.5, the reaction rate of the relevant components can be effectively increased, and the alkaline environment of the reaction system can be maintained, thereby promoting the reaction between thiocyanate and thiol compounds.

[0063] For example, by controlling the molar amount of the solvent to 23300-23350, the solvent can fully wet other components and make the components mutually soluble to form a relatively uniform mixed system, which is convenient for preparing the polymer resin.

[0064] In some embodiments, the thiocyanate can be selected from one or more of phenylene diisothiocyanate, p-phenylene diisothiocyanate, p-xylylene diisothiocyanate, and pyridine diisothiocyanate.

[0065] In some embodiments, the thiol compound can be selected from one or more of 4,4-diaminodiphenyl sulfide, 4,4-dimercaptodiphenyl ether, 4,4-dimercaptodiphenyl disulfide, and 2,4-dimercapto-6-amino-1,3,5-triazine.

[0066] In some embodiments, the organic base catalyst can be selected from one or more of triethanolamine (TEA), triphenylamine (TPA), 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), 4-dimethylaminopyridine (DMAP), 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD), 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (MTBD), and pyridine.

[0067] In some embodiments, the solvent may be one or more of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), and N-methyl-2-pyrrolidone (NMP).

[0068] The following is a description of the preparation method of the polymer resin of the present application comprising the aforementioned multiple components.

[0069] like Figure 1 As shown, the present application embodiment also provides a method for preparing a polymer resin, comprising the following steps:

[0070] S101, providing thiocyanate, a thiol compound, an organic base catalyst and a solvent;

[0071] S102, stirring thiocyanate, mercapto compound, organic base catalyst and solvent uniformly to react and obtain polymer resin.

[0072] It should be noted that the specific examples of thiocyanate, mercapto compound, organic base catalyst and solvent can refer to the above examples, which will not be repeated here.

[0073] In the embodiment of the present application, raw materials such as thiocyanate, thiol compound, organic base catalyst and solvent are stirred evenly for reaction, and a polymer resin including thioamide group, thioether group and aromatic group can be obtained, so that the polymer resin has a high refractive index, good light transmittance and good mechanical properties, heat resistance and low shrinkage. Moreover, the raw materials provided by the present application are easy to obtain, highly active, and simple in reaction conditions. Only organic base catalysts are used, and no organic metal catalyst is required to react to obtain a polymer resin, and hydrogen bond acceptors and hydrogen bond donors are both located in the main chain structure of the polymer resin. The introduction process does not require additional modification steps, thereby simplifying the synthesis process, reducing the process difficulty and production cost. Moreover, since the preparation method can directly embed hydrogen bond acceptors and hydrogen bond donors into the main chain, it can also optimize its solubility, improve the molecular weight of the polymer resin, and improve its thermal stability and processing performance. In addition, since hydrogen bond acceptors and hydrogen bond donors are directly embedded in the main chain structure of the polymer resin, the active sites can be greatly reduced or eliminated, thereby improving the antioxidant and stability of the polymer resin and reducing the probability of yellowing.

[0074] In some embodiments, in step S102, thiocyanate, thiol compound, organic base catalyst and solvent are stirred evenly to react, the reaction temperature of the reaction is 22-24°C, the reaction time of the reaction is 23.5-24.5 hours, and the reaction environment of the reaction is a nitrogen environment.

[0075] By controlling the reaction temperature of the above raw materials to 22-24° C., the reaction time to 23.5-24.5 hours and the reaction environment to be a nitrogen environment, thiocyanate and mercapto compounds can be fully reacted, and the activities of thiocyanate and mercapto compounds are relatively high, and the reaction promotion effect of the organic base catalyst can be better, so that the prepared polymer resin has a high refractive index, good antioxidant properties, stability, light transmittance, as well as good mechanical properties, heat resistance and low shrinkage.

[0076] Preferably, the reaction temperature is 23° C. and the reaction time is 24 hours.

[0077] Exemplarily, after thiocyanate, thiol compound, organic base catalyst and solvent are stirred evenly for reaction, the reaction solution is filtered through a filter to remove solid insoluble matter, and the filtrate is added dropwise into methanol for precipitation. The precipitate is filtered and then washed with methanol, and then dried in a vacuum environment at 40°C to obtain a polymer resin.

[0078] An embodiment of the present application also provides an optical lens, in which a diffraction optical waveguide structure is installed. The substrate in the diffraction optical waveguide structure is made of the polymer resin described in any of the above embodiments, or is made of a polymer resin prepared by the method for preparing the polymer resin described in any of the above embodiments.

[0079] An embodiment of the present application also provides a pair of smart glasses, which include the optical lenses described in any of the above embodiments.

[0080] The embodiments of the present application are described below through specific examples.

[0081] Embodiment 1:

[0082] Under nitrogen environment, p-phenylene diisocyanate (576.8 mg, 3 mmol), 4,4'-dimercaptodiphenyl sulfide (751.2 mg, 3 mmol), and 1,8-diazabicyclo[5.4.0]undec-7-ene (2 uL, 0.015 mmol) were added to a 100 mL three-necked reaction bottle equipped with a magnetic stirring bar. Then DMF (18 mL) was injected with a syringe to dissolve the above raw materials, and the stirring was continued at room temperature (23° C.) for 24 hours. The solution after the reaction was filtered to remove the solid insoluble matter, and the filtrate was added dropwise to 250 mL of methanol for precipitation. The precipitate was filtered and washed three times with methanol, and then dried under a vacuum environment of 40° C. to obtain a polymer resin P1.

[0083] In this embodiment, the raw material components are shown in Table 1.

[0084] Table 1

[0085]

[0086] In this embodiment, the structural formula of the obtained polymer resin P1 is:

[0087]

[0088] Embodiment 2:

[0089] Under nitrogen environment, p-phenylene diisocyanate (480.7 mg, 2.5 mmol), 2,4-dimercapto-6-amino-1,3,5-triazine (400.2 mg, 2.5 mmol), and 1,8-diazabicyclo[5.4.0]undec-7-ene (1.3 uL, 0.01 mmol) were added to a 100 mL three-necked reaction bottle equipped with a magnetic stirring bar. Then, DMF (mL) was injected with a syringe to dissolve the above raw materials, and the stirring was continued at room temperature (23° C.) for 24 hours. The solution after the reaction was filtered to remove the solid insoluble matter, and the filtrate was added dropwise to 250 mL of methanol for precipitation. The precipitate was filtered and washed three times with methanol, and then dried under a vacuum environment of 40° C. to obtain a polymer resin P2.

[0090] In this embodiment, the raw material components are shown in Table 2.

[0091] Table 2

[0092]

[0093] In this embodiment, the structural formula of the obtained polymer resin P2 is:

[0094]

[0095] Embodiment 3:

[0096] Under nitrogen environment, pyridine diisocyanate (672.9 mg, 3.5 mmol), 4,4'-dimercaptodiphenyl sulfide (751.2 mg, 3 mmol), and 1,8-diazabicyclo[5.4.0]undec-7-ene (2.7 uL, 0.02 mmol) were added to a 100 mL three-necked reaction bottle equipped with a magnetic stirring bar. Then DMF (20 mL) was injected with a syringe to dissolve the above raw materials, and the stirring was continued at room temperature (23° C.) for 24 hours. The solution after the reaction was filtered to remove the solid insoluble matter, and the filtrate was added dropwise to 250 mL of methanol for precipitation. The precipitate was filtered and washed three times with methanol, and then dried under a vacuum environment of 40° C. to obtain a polymer resin P3.

[0097] In this embodiment, the raw material components are shown in Table 3.

[0098] Table 3

[0099]

[0100] In this embodiment, the structural formula of the obtained polymer resin P3 is:

[0101]

[0102] Embodiment 4:

[0103] Under nitrogen environment, pyridine diisocyanate (579.8 mg, 3 mmol), 2,4-dimercapto-6-amino-1,3,5-triazine (560.2 mg, 3.5 mmol), and 1,8-diazabicyclo[5.4.0]undec-7-ene (2.4 uL, 0.018 mmol) were added to a 100 mL three-necked reaction bottle equipped with a magnetic stirring bar. Then DMF (20 mL) was injected with a syringe to dissolve the above raw materials, and the stirring was continued at room temperature (23° C.) for 24 hours. The solution after the reaction was filtered to remove the solid insoluble matter, and the filtrate was added dropwise to 250 mL of methanol for precipitation. The precipitate was filtered and washed three times with methanol, and then dried under a vacuum environment of 40° C. to obtain a polymer resin P4.

[0104] In this embodiment, the raw material components are shown in Table 4.

[0105] Table 4

[0106]

[0107] In this embodiment, the structural formula of the obtained polymer resin P4 is:

[0108]

[0109] Comparative Example:

[0110] The polymer resin P5 is prepared by introducing hydroxyl groups into the benzene ring of polyphenylene sulfide.

[0111] Test example:

[0112] The resin performance parameters of the polymer resins P1-P4 prepared in Examples 1-4 and the polymer resin P5 provided in the comparative example, such as refractive index, Abbe number, water absorption, light transmittance, glass transition temperature (Tg) and yellowness index, are tested. The results are shown in Table 5.

[0113] The compounds prepared in the above Examples 1 to 4 and the comparative examples (i.e., polymer resins P1 to P6) were subjected to the following tests:

[0114] 1. Refractive index test. The purified resin is dispersed in a polar solvent, such as tetrachloroethane, and then spin-coated on a silicon wafer by spin coating. After baking, the refractive index is tested using an ellipsometer. The refractive indexes of the compounds prepared in Examples 1 to 4 and the comparative examples are shown in Table 5.

[0115] 2. Abbe number test. The Abbe number is calculated by the refractive index at wavelengths of 486.nm, 587.6nm and 656.3nm. The calculation formula is as follows:

[0116] Vd=(nD-1) / (nF-nC)

[0117] The Abbe numbers of the compounds prepared in Examples 1 to 4 and the comparative examples are shown in Table 5.

[0118] 3. Water absorption test. The compounds prepared in Examples 1 to 4 and the comparative example were injected to obtain 2 mm thick plate-shaped molded sheets, and the water absorption after immersion at 23°C for 24 hours was measured according to ISO62. The water absorption of the compounds prepared in Examples 1 to 4 and the comparative example after testing is shown in Table 5.

[0119] 4. Light transmittance test. The purified resin is dispersed in a polar solvent, such as tetrachloroethane, and then spin-coated on the surface of a glass substrate by spin coating. After baking, the haze meter is used for testing. The light transmittances of the compounds prepared in Examples 1 to 4 and the comparative examples are shown in Table 5.

[0120] 5. Glass transition temperature (Tg) test. The test was conducted using a 2910 differential scanning calorimeter manufactured by TA Instruments Japan at a heating rate of 10°C / min. The glass transition temperatures (Tg) of the compounds prepared in Examples 1 to 4 and the comparative examples are shown in Table 5.

[0121] 6. Yellowness index test.

[0122] Table 5

[0123]

[0124] It can be seen that, since the thioamide group contains an NH bond and the thioether group contains a sulfur atom, the refractive index of the polymer resins P1-P4 obtained in Examples 1-4 is above 1.816, which means that the polymer resins provided in the examples of the present application have an ultra-high refractive index; the Abbe numbers of the polymer resins P1-P4 are all above 18, which means that the optical lenses made of the polymer resins provided in the examples of the present application have small dispersion and clear imaging; the water absorption rates of the polymer resins P1-P4 are all above 0.1%, and the polymer resins will swell into hydrogels after absorbing water. In this state, it is difficult to separate water from the resin even if pressurized, thereby maintaining the stability and integrity of the resin, which helps to prevent the resin from being damaged by water during use. The performance degradation caused by the loss of light is reduced, thereby extending its service life; the light transmittance of the polymer resins P1-P4 is all above 84%; the Tg of the polymer resins P1-P4 is all above 150°C, which means that the thermal stability of the polymer resins provided in the embodiments of the present application is good; the yellowness index of the polymer resins P1-P4 is all lower than 1.90, while the polymer resin P5 of the comparative example reaches 1.92. Therefore, the antioxidant capacity of the polymer resins P1-P4 provided in the present application is higher than that of the polymer resin P5 of the comparative example, that is, the polymer resin provided in the present application has a higher refractive index, good light transmittance, good mechanical properties, heat resistance and low shrinkage, and the polymer resin has excellent antioxidant property and stability.

[0125] It should be understood that the terms used in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application.

[0126] It should also be understood that the term “and / or” used in the specification and appended claims refers to any and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0127] The above is only a specific embodiment of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and these modifications or replacements should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A polymer resin, characterized in that The polymer resin has the following general structural formula: In the formula, at least one of R1 and R2 is an aromatic group, and n is a positive integer of 1-10000.

2. The polymer resin according to claim 1, characterized in that R1 and R2 are both aromatic groups.

3. The polymer resin according to claim 1, characterized in that The aromatic group is at least one of a benzene ring, a naphthalene ring, fluorene, carbazole, furan, thiophene, pyrrole, thiazole, imidazole, pyridine, pyrazine, pyrimidine and pyridazine.

4. The polymer resin according to claim 1, characterized in that The polymer resin is selected from the structural formula: or, or, or, Any one of the compounds in .

5. A polymer resin, characterized in that The polymer resin is prepared from the following raw materials: thiocyanate, mercapto compound, organic base catalyst and solvent.

6. The polymer resin according to claim 5, characterized in that The molar ratio of the thiocyanate, the mercapto compound, the organic base catalyst and the solvent is (300-350):300:(1-2):(23000-24000).

7. The polymer resin according to claim 5, characterized in that The thiocyanate is at least one of phenylene diisothiocyanate, p-phenylene diisothiocyanate, p-xylylene diisothiocyanate, and pyridine diisothiocyanate.

8. The polymer resin according to claim 5, characterized in that The mercapto compound is at least one of 4,4-dimercaptodiphenyl ether, 4,4-dimercaptodiphenyl disulfide, and 2,4-dimercapto-6-amino-1,3,5-triazine.

9. A method for preparing a polymer resin, characterized in that: The method comprises: Providing thiocyanate, mercapto compound, organic base catalyst and solvent; The thiocyanate, the mercapto compound, the organic base catalyst and the solvent are stirred uniformly to react to obtain a polymer resin.

10. The method according to claim 9, characterized in that The reaction temperature of the reaction is 22-24° C., the reaction time of the reaction is 23.5-24.5 hours, and the reaction environment of the reaction is a nitrogen environment.

11. An optical lens, characterized in that: The optical lens is made of the polymer resin described in any one of claims 1 to 8, or is made of the polymer resin obtained by the method for preparing the polymer resin described in claim 9 or 10.

12. A smart glasses, characterized in that: The smart glasses include the optical lenses as claimed in claim 11.

Citation Information

Cited By

  • Polythionocarbamate resin, preparation method and application

    CN120965961A

  • Polymer resin and preparation method therefor, optical lens, and smart glasses

    WO2026137724A1